Recurrent Ameloblastoma: Clinical Manifestation and Disease-Free Survival Rate. (9th August 2022) - Hresko, Andrii; Palyvoda, Roman; Burtyn, Olha; Chepurnyi, Yurii; Kopchak, Andrii; Helder, Marco; Forouzanfar, Tymour
Abstract : Objectives . Ameloblastoma is a slow-growing epithelial odontogenic neoplasm of the jaws with a high recurrence rate. The main treatment strategies for this lesion are radical or conservative surgical approaches. The aim of the present study was to analyze clinical presentations, histological types, and treatment strategies of recurrent ameloblastoma and to define its disease-free survival (DFS) rate. Materials and Methods . Twenty-four cases of recurrent ameloblastomas, treated between January 2009 and July 2021, were enrolled in this study. Medical files from each patient, including gender, age, size of the lesion, localization, patient complaints, clinical manifestation, radiographic appearance, histological type, surgical management, and treatment results were reviewed and analyzed retrospectively. Result . Out of 69 operated primary ameloblastomas, the rate of recurrence was 35%. Out of 24 recurrent cases, 21 developed after conservative treatment and 3 after radical treatment. In most cases, recurrences were found in the mandible ( n = 20). A unilocular pattern was predominant in radiographic examination (44%). Estimated 3-year DFS was 84.5 ± 4.8%, and the 5-year and 10-year DFS were 73.0 ± 6.3% and 43.9 ± 8.343.9 ± 8.3%, respectively. Conclusion . Results obtained in the present retrospective study proved the necessity of long-term follow-up after both conservative and radical treatment approaches. The DFS median in our study was 8 years (95% CI 6 years–10 years). For recurrent cases, radical resection with histologically free margins after exact MRI determination of the ameloblastoma border within the soft tissues should be considered as the method of choice to avoid secondary recurrence.